АНАЛИЗ МЕЖДУНАРОДНОГО ОПЫТА ПОДГОТОВКИ КАДРОВ В ОБЛАСТИ КИБЕРЗАЩИТЫ - Сеитназаров, К.К.; Уримбетова, З.А. (SCIENCE and SOCIETY, 2025)
The article presents materials on the problem of forming cybersecurity in the educational system, and also provides an analysis of international experience in training personnel in the field of cyber protection and the inclusion of its basics in all levels of education for modeling and formation of professional skills.
Keywords: cyber protection; cybersecurity; analysis; education; digital literacy; competence